Promoting Cassava as an Industrial Crop in Ghana: Effects on Soil Fertility and Farming System Sustainability - S. Adjei-Nsiah; Owuraku Sakyi-Dawson (Applied and Environmental Soil Science)
Cassava is an important starchy staple crop in Ghana with per capita consumption of 152.9 kg/year. Besides being a staple food crop, cassava can be used as raw material for the production of industrial starch and ethanol. The potential of cassava as an industrial commercial crop has not been exploited to a large extent because of perceptions that cassava depletes soils. Recent finding from field studies in the forest/savannah transitional agroecological zone of Ghana indicates that when integrated in the cropping system as a form of rotation, cassava contributes significantly to maintenance of soil fertility, and thus large scale production of cassava for industrial use can contribute to poverty reduction in an environmentally responsive way. This paper discusses the role of cassava cultivation in soil fertility management and its implication for farming system sustainability and industrialization.